Income Effects and the Theory of the Firm - de V. Graaff, J. (Review of Economic Studies, 1950)
Income Effects and the Theory of the Firm J. de V. Graaf J. de V. Graaf Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 2, 1950, Pages 79–86, https://doi.org/10.2307/2295795 Published: 01 April 1950